The paradox of novelty and continuity of the 2022 National Elections in Costa Rica - Pignataro López, Adrián (2023)
The article introduces the special issue on the 2022 Elections in Costa Rica. It discusses how old trends (fragmentation, low turnout, among others) combine with new elements (victory of an outsider). The electoral political dynamics since 1953 are summarized in a latent variable model, which reflects the new political-electoral era that began in 2002 and the unusual nature of the 2018 and 2022 elections.